Influence of fatigue on running coordination: A UCM analysis with a geometric 2D model and a subject-specific anthropometric 3D model - Möhler, Felix; Ringhof, Steffen; Debertin, Daniel; Stein, Thorsten (Human movement science, 2019)
•We studied the effects of fatigue during running on the control of the center of mass (CoM) trajectory.•To do so, we used the uncontrolled manifold (UCM) approach.•We used a geometric 2D model and a subject-specific anthropometric 3D model.•Results show minor effects of fatigue on CoM trajectory.•Slight effects of fatigue were detected with the 3D model. Although fatigue is a central issue in endurance sports little is known about the effects of fatigue on coordination. The uncontrolled manifold (UCM) approach has been widely used in recent studies to examine coordination in human movement; however, it has not been used to study the effects of fatigue on running. Therefore, the aim of this study was to analyze the effects of fatigue on the synergy structure stabilizing the center of mass (CoM) trajectory in experienced runners during high-intensity running using the UCM approach. A total of 13 healthy young experienced runners participated in the study. Based on a lactate threshold testing undertaken one week prior to the measurements, participants were asked to run on a treadmill at their individual “fatigue-speed” until exhaustion. The kinematics of 20 consecutive gait cycles were recorded at the beginning (rested) and at the end (fatigue) of the protocol. The effects of fatigue on the synergy structure were investigated using a geometric 2D model and a subject-specific anthropometric 3D model. Specifically, the variance affecting the CoM trajectory (UCM⊥), the variance not affecting the CoM trajectory (UCM‖), and their ratio (UCMRatio) were analyzed for different gait cycle phases (absorption, propulsion and flight phase). Three-way repeated-measures ANOVA tests revealed differences between the two models. Fatigue-induced changes in the UCM structure could only be detected using the 3D model. UCMRatio did not change, but UCM⊥ increased during flight phase. In the 2D model, UCMRatio and both components were higher during the propulsion phase than during the absorption phase in both the rested and the fatigued state. Using a current concept for analyzing motor coordination, the UCM approach, only minor changes with fatigue were detected using the 3D subject-specific model. This indicates that the runners were able to control the trajectory of their CoM when fatigued. As the 2D model was not able to detect these changes, our study emphasizes that future studies on the effects of fatigue should focus on 3D analyses.